1983
DOI: 10.1152/jn.1983.50.6.1359
|View full text |Cite
|
Sign up to set email alerts
|

Fast ballistic arm movements triggered by visual, auditory, and somesthetic stimuli in the monkey. II. Effects of unilateral dentate lesion on discharge of precentral cortical neurons and reaction time

Abstract: Single-unit recordings from motor cortex (area 4) were obtained before and after dentate lesion in two monkeys executing fast elbow flexions and extensions in response to randomly presented visual, auditory, and somesthetic stimuli. There were no starting or ending reference points or preparatory signals. Monkeys were trained to perform movements larger than 15 degrees within 500 ms of the stimulus presentation. After electrolytic lesion of the dentate nucleus ipsilateral to the trained arm, changes in reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
26
1
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 0 publications
7
26
1
1
Order By: Relevance
“…A strategy of single-digit winkling when permitted was often successful. These observations also agree with previous observations (Bastian and Thach 1995;Thach et al 1992).…”
Section: Deficits In the Performance Of The Unconstrained Compound Tasksupporting
confidence: 94%
See 4 more Smart Citations
“…A strategy of single-digit winkling when permitted was often successful. These observations also agree with previous observations (Bastian and Thach 1995;Thach et al 1992).…”
Section: Deficits In the Performance Of The Unconstrained Compound Tasksupporting
confidence: 94%
“…The magnitude of the increase in reaction time was not significantly different for ThumbϩIndex than for Thumb or Index tasks. This finding agrees with most studies of simple movements which have reported an increase in reaction time following inactivation of the dentate nucleus (MeyerLohmann et al 1977;Mink and Thach 1991;Thach et al 1992;Trouche and Beaubaton 1980). There was no observed weakness after inactivation.…”
Section: Deficits In the Performance Of The Constrained Digit Taskssupporting
confidence: 92%
See 3 more Smart Citations